2010
DOI: 10.1063/1.3493154
|View full text |Cite
|
Sign up to set email alerts
|

Self-biased magnetoelectric response in three-phase laminates

Abstract: Articles you may be interested in Self-biased large magnetoelectric coupling in co-sintered Bi0.5Na0.5TiO3 based piezoelectric and CoFe2O4 based magnetostrictive bilayered composite J. Appl. Phys. 116, 244101 (2014) This study reports the experimental observation and analysis of self-biased magnetoelectric ͑ME͒ effect in three-phase laminates. The 2-2 L-T mode laminates were fabricated by attaching nickel ͑Ni͒ plates and ME particulate composite plates having 3-0 connectivity with 0.948Na 0.5 K 0.5 NbO 3 -0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 13 publications
1
55
0
Order By: Relevance
“…The Ni provided a field to bias the ME sensor. 10,11 The measuring system consisted of a set of Helmholtz coils, powered by an Agilent 33220 A signal generator that was used to apply a sinusoidal, time varying field H s along the longitudinal axis of the sensor. In these experiments, we did not employ any flux concentrators.…”
Section: Methodsmentioning
confidence: 99%
“…The Ni provided a field to bias the ME sensor. 10,11 The measuring system consisted of a set of Helmholtz coils, powered by an Agilent 33220 A signal generator that was used to apply a sinusoidal, time varying field H s along the longitudinal axis of the sensor. In these experiments, we did not employ any flux concentrators.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have revealed that by employing heterogeneous ferromagnetic structure, a large a DME value can be obtained in the absence of H bias , so called self-biased DME effect. [8][9][10] The selfbiased DME effect was observed when the laminates were operated in bending mode and consisted of dissimilar or graded magnetic materials that resulted in built-in magnetic bias. The discovery of self-biased DME effect is encouraging for applications such as self-biased magnetic field sensor.…”
mentioning
confidence: 99%
“…9 ] (KNNLS-NZF) ME particulate composite disks with diameter of 10 mm and thickness of 0.5 mm were fabricated. The built-in magnetic bias was created in the sandwich structure (nickel (Ni) plate with dimensions of 15 Â 15 Â 0.5 mm 3 bonded between two KNNLS-NZF disks) due to difference in magnetic characteristics between Ni and NZF such as magnetization, susceptibility, coercivity, magnetostriction, and piezomagnetic coefficient.…”
mentioning
confidence: 99%
See 2 more Smart Citations